Female Education and Fertility Differentials by Religion in Murshidabad District, West Bengal - Chowdhury, Md. Asgar Hossain; Siddiqui, Farasat Ali (National Geographical Journal of India, 2022)
Education is one of the most important factors indirectly affecting fertility behaviour and believed to be the single most important variable accounting for a large reduction in fertility. The present paper tries to investigate the relationship between female education and religious fertility differentials in Murshidabad district, West Bengal. The study is based on primary sources of data collected through a household survey. Mean Child Ever Born (MCEB) is one of the measures of fertility, which is applied to find out fertility rates by female education and religion (Muslim and Hindu). Choropleth maps and bar graphs have been prepared to highlight spatial patterns of fertility. The finding reveals that advancement in female education helps in reducing the fertility rate in Murshidabad district.